2019
DOI: 10.1016/j.jjcc.2019.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Medium- and long-term follow-up of transcatheter closure of ruptured sinus of Valsalva aneurysm in Central Europe population

Abstract: Sinus of Valsalva aneurysm (SVA) is an uncommon and mostly congenital cardiac anomaly which predominantly affects Asian males [1]. Congenital SVA is caused by deficiency of normal elastic tissue between aortic media and the annulus fibrosus (abnormal bulbus cordis development) [2]. Ventricular septal defect (VSD), aortic regurgitation (AR), and bicuspid aortic valve (BAV) are frequent concomitant lesions in this SVA type. Acquired SVA can result from previous cardiac surgery, endocarditis, syphilis, atheroscle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 27 publications
0
10
0
1
Order By: Relevance
“…However, an increasing number of transcatheter closures are being described ( 6 ). Despite favorable outcomes of surgical repair, transcatheter closure remains a good alternative for patients with a small ruptured area and no concomitant heart defects requiring surgery ( 11 , 12 ). The prevalence of ruptured SVA is low compared to other heart defects that can be percutaneously repaired, thus, there are no commercially available devices dedicated to SVA repair.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, an increasing number of transcatheter closures are being described ( 6 ). Despite favorable outcomes of surgical repair, transcatheter closure remains a good alternative for patients with a small ruptured area and no concomitant heart defects requiring surgery ( 11 , 12 ). The prevalence of ruptured SVA is low compared to other heart defects that can be percutaneously repaired, thus, there are no commercially available devices dedicated to SVA repair.…”
Section: Discussionmentioning
confidence: 99%
“…The device used in the case presented above was primarily designed to repair a patent ductus arteriosus. Other types of device have also been successfully used ( 6 , 12 , 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…The operative mortality rate is 1.9%-3.6% with 90% survival at 15 years [3]. The accurate mortality associated with percutaneous closure of ruptured SVA could not be determined due to paucity of large-scale data, but multiple studies have shown good outcomes in select patients [10][11][12][13]. The choice of percutaneous vs surgical intervention depends on multiple factors, including patient's age, comorbidities, hemodynamic status at presentation, coexisting congenital heart defects like ventricular septal defects, aortic regurgitation, underlying obstructive coronary artery disease, size of ruptured SVA, and location in addition to the local cardiac surgeon and interventional cardiologist's expertise.…”
Section: Discussionmentioning
confidence: 99%
“…Our experiences in percutaneous closure of ruptured sinuses of Valsalva aneurysm (RSVA) with various devices like ADOI and ASO were described in several papers reflecting various stages of our growing experience and longer patient observation. The last paper (published together with colleagues from the Amosov In stitute in Kyiv, Ukraine) summarized results of RSVA closure in 23 patients, which is one of the largest reported cohorts [15]. We concluded that percutaneous closure of RSVA is (1) safe and effective, however, recanalizations are possible (in a different location); (2) it is also suitable for a second percutaneous attempt.…”
Section: Vascular Malformationsmentioning
confidence: 98%